2015
DOI: 10.1088/0022-3727/48/43/434001
|View full text |Cite
|
Sign up to set email alerts
|

Co-precipitation of oppositely charged nanoparticles: the case of mixed ligand nanoparticles

Abstract: Colloid stability is of high importance in a multitude of fields ranging from food science to biotechnology. There is strong interest in studying the stability of small particles (of a size of a few nanometres) with complex surface structures, that make them resemble the complexity of proteins and other natural biomolecules, in the presence of oppositely charged nanoparticles. While for nanoparticles with homogeneously charged surfaces an abrupt precipitation has been observed at the neutrality of charges, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The shaded area shows a conservative estimate of the indeterminacy with which the pKa of the ligand in water is known: the free ligand has a pKa of 5 (bottom edge of the shaded area for z = 3 nm from the membrane center), while cooperative effects on the NP surface have been predicted to shift the pK a of similar ligands up to 7.6 34 (upper edge of the shaded area). Using 6.3 as reference pK a value in water 35 , the light-blue profile is obtained and the error bars deriving from our metadynamics calculations lay within the shaded area. The shaded grey areas indicate the distribution of lipid heads and glycerol groups.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The shaded area shows a conservative estimate of the indeterminacy with which the pKa of the ligand in water is known: the free ligand has a pKa of 5 (bottom edge of the shaded area for z = 3 nm from the membrane center), while cooperative effects on the NP surface have been predicted to shift the pK a of similar ligands up to 7.6 34 (upper edge of the shaded area). Using 6.3 as reference pK a value in water 35 , the light-blue profile is obtained and the error bars deriving from our metadynamics calculations lay within the shaded area. The shaded grey areas indicate the distribution of lipid heads and glycerol groups.…”
Section: Resultsmentioning
confidence: 88%
“…We set up surface have been predicted to shift the pKa of similar ligands up to 7.6 34 (upper edge of the shaded area). Using 6.3 as reference pKa value in water 35 , the light-blue profile is obtained and the error bars deriving from our metadynamics calculations lay within the shaded area. The shaded grey areas indicate the distribution of lipid heads and glycerol groups.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In fact, because of their nanometer scales, NPs are characterized by an extremely high surface-to-volume ratio and, therefore, NPs in solution tend to aggregate to minimize the surface energy, resulting in the rapid settling of the suspension. 1 Numerous previous studies have focused on the role of charges, 20 solvent ion concentration, 21 solubility, and wettability, 22 and it has been demonstrated that the charge and morphology of the ligand shell play a fundamental role on determining NPs' properties. 23 In particular, the role of ions in promoting NP aggregation has been thoroughly investigated 24,25 in large part due to the well-known ability of multivalent cations to bridge charged ligands and to promote NP aggregation.…”
Section: Introductionmentioning
confidence: 99%